2021
DOI: 10.3390/ma14040770
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Citrazinic Acid Ions and Their Contribution to Optical and Magnetic Features of Carbon Nanodots: A Combined Experimental and Computational Approach

Abstract: The molecular model is one of the most appealing to explain the peculiar optical properties of Carbon nanodots (CNDs) and was proven to be successful for the bottom up synthesis, where a few molecules were recognized. Among the others, citrazinic acid is relevant for the synthesis of citric acid-based CNDs. Here we report a combined experimental and computational approach to discuss the formation of different protonated and deprotonated species of citrazinic acid and their contribution to vibrational and magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
(75 reference statements)
4
10
0
Order By: Relevance
“…Indeed, if we consider the case of IPCA, a reaction of cyclization between CA and ethylene-diamine was hypothesized to produce the molecule that acts as a seed for the formation of the CDs and cause, with its aggregates, the excitation dependent emission features recorded in those systems [28,67,68]. In a similar way, we recently studied the formation of CZA in the synthesis of CA and urea (the reference system in the present study) and we demonstrated that the formation of various ionic species and different aggregates can explain the optical features of citric acid derived CDs [65,66,69,70]. If we assumed the same reaction paths reported for CZA and IPCA, more than one product could be embedded during the CD formation.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Indeed, if we consider the case of IPCA, a reaction of cyclization between CA and ethylene-diamine was hypothesized to produce the molecule that acts as a seed for the formation of the CDs and cause, with its aggregates, the excitation dependent emission features recorded in those systems [28,67,68]. In a similar way, we recently studied the formation of CZA in the synthesis of CA and urea (the reference system in the present study) and we demonstrated that the formation of various ionic species and different aggregates can explain the optical features of citric acid derived CDs [65,66,69,70]. If we assumed the same reaction paths reported for CZA and IPCA, more than one product could be embedded during the CD formation.…”
Section: Discussionsupporting
confidence: 62%
“…The whole set of experimentally observed features here reported calls for the formation of CDs: the rounded nanoparticle observed by means of TEM (mean size 5-12 nm), the measured D and G vibrational bands, the absorption band around 350 nm, the excitation dependent emission spectra and the non-single exponential decay times. As already proposed for parent CA derived systems, those features are related to the formation of some specific molecule, as the IPCA and CZA molecules reported in those cases [11,28,65,66]. Starting from this consideration, we hypothesized that the pyridinone molecules produced during the synthesis of CA and hydrazine, their aggregated forms or some polymeric structure derived by further reactions of the monomer units can be incorporated into the structure of the CDs and produce the optical…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Indeed the Fourier-transform infrared spectrum reported by Sarkar do show two large bands that could be partly related to H-bonding between monomer units besides the larger contribution of OH groups typically found in this vibrational range that hampers the Raman analysis of CZA water solution down to 3500 cm –1 . In a very recent paper, we showed that, besides the formation of different ionic species, aggregation is also important for the magnetic features of CZA-related carbon nanodots …”
Section: Resultsmentioning
confidence: 99%
“…In a very recent paper, we showed that, besides the formation of different ionic species, aggregation is also important for the magnetic features of CZA-related carbon nanodots. 51 3.6. Raman and IR Spectra.…”
Section: Experimental and Computationalmentioning
confidence: 99%